Vigiando, divulgando e reprimindo: o papel da imprensa no cotidiano dos moradores de Belém (1897-1910) - GOMES, João Arnaldo Machado (Universidade Federal do Pará, 2017)
The center of discussion in this research is the theme of social control exercised by the economic and political elites in Belém that was intended to modernize and civilize during the municipal management of intendant Antônio Lemos between the years of 1897 to 1910. Seen from the perspective of the press, the proposal was try to understand how the exercise of this control was reinforced, in a particular way, by the newspapers The Province of Pará and Leaf of the North, trough the daily publication of police chronicles that reported from crimes to transgressions occurred in the urban space. The objective is to understand the dynamics of the relationship between the two newspapers and the ideals of civility and modernity defended by the elites in the exercise of repression of popular habits and customs through the dissemination of news that denounced spaces and individuals considered suspects in order to perceive how the different layers of society interacted in the urban environment, and how police work developed in the daily of the city in dealing with the population in general.